The Influence of Work Motivation, Work Discipline, and Work Environment on Employee Performance at PT. Prima Medan Lestari - Sindya Rani; Muhammad Yalzamul Insan; Eli Delvi Yanti (Utan Kayu Publishing, 2026)
This research endeavors to ascertain how employee performance at PT. Prima Medan Lestari is influenced by work motivation, work discipline, and the work environment. All the workers at PT. Prima Medan Lestari constitute the focus of this research. The year this investigation took place was 2025. Using a saturated sampling approach, the study included a sample and population of 40 respondents. The data were processed utilizing SPSS version 24. Classical assumption tests and multiple linear regression ana lysis were among the data analysis strategies used. According to the research findings, the t-test for the work motivation variable (X1) reveals a t-value of 7.722, which is greater than the t-table value of 2.028, and a significance value of 0.000, which is less than 0.05, suggesting that, in part, work motivation has a favorable and noteworthy impact on how well employees perform. The t-test result for the work discipline variable (X2) indicates a t-value of 2.727, which exceeds the t-table value of 2.028, alongside a significance value of 0.008, which is less than 0.05, implying that work discipline, in isolation, exerts a beneficial and substantial influence on employee performance. Regarding the work environment variable (X3), the t-test yields a t-value of 2.213, which is greater than the t-table value of 2.028, and a significance value of 0.033, which is less than 0.05, thereby signifying that the work environment, in part, positively and significantly affects employee performance. The outcome of the F-test reveals that the computed F-statistic of 27.099 surpasses the F-critical value of 2.641, accompanied by a noteworthy significance level of 0.000, which is less than the threshold of 0.05. The R- squared value, which measures the proportion of variance explained, stands at 0.668, or 66.8%, signifying the extent to which the predictor variables, namely work motivation (X1), work discipline (X2), and work environment (X3), account for the variation observed in the employee performance variable (Y).The outcomeoftheF-testreveals thatthe computed F-statistic of27.099 surpassestheF-critical value of2.641, accompanied byanoteworthysignificancelevel of0.000, which islessthanthethreshold of0.05. The R-squared value, which measures the proportion of variance explained, stands at 0.668, or 66.8%, signifying the extent to whichthepredictor variables, namely work motivation (X1), work discipline (X2), and work environment (X3), account for the variationobserved in the employee performance variable (Y).